Formulation of Mineral Salt and Milkfish Bone (Chanos chanos) Waste to Prevent Preeclampsia - Selpida Handayani; Aminah Aminah; Nurmaya Effendi; Andi Elis; Rais Razak; Wiyuwarmi Wiyuwarmi; Miftahul Khaira; Dedy Putra Wahyudi; Fitriani Umar (Pharmaceutical Reports, 2026)
The high rate of maternal mortality remains a significant public health concern, highlighting the urgent need to improve maternal health, particularly during pregnancy. One of the major complications contributing to maternal morbidity and mortality is preeclampsia, a pregnancy-related disorder characterized by hypertension, proteinuria, and edema. Nutritional deficiencies, especially in essential minerals such as potassium, magnesium, and calcium, have been identified as contributing factors in the development of preeclampsia. Therefore, ensuring adequate intake of these micronutrients is crucial for prevention and maternal well-being. This study aimed to analyze the mineral content of a formulated mineral salt derived from milkfish (Chanos chanos) bone waste as a potential alternative source of essential nutrients. The research employed an experimental laboratory method, with mineral analysis conducted using an Atomic Absorption Spectrophotometer (AAS). The formulation was evaluated for its potassium, magnesium, and calcium content to determine its potential contribution to daily nutritional requirements. The results showed that a daily intake of 5 grams of the formulated product could provide approximately 1.49% of potassium, 45% of magnesium, and 65.26% of calcium requirements. These findings indicate that the mineral salt formulation derived from milkfish bone waste is particularly rich in calcium and magnesium, both of which play important roles in maintaining vascular function and reducing the risk of hypertensive disorders during pregnancy. In conclusion, the developed mineral salt formulation has promising potential as a non-pharmacological preventive strategy to support micronutrient intake in pregnant women. Its utilization may contribute to reducing the risk of preeclampsia and improving maternal health outcomes. Further studies are recommended to evaluate its safety, bioavailability, and clinical effectiveness.